Violent attacks on education in the tribal areas of Pakistan and the role of NGOs in providing educational services. Issue 2 (4th March 2018) - Khan, Muhammad Ammad; Kanwal, Nazish; Wang, Libin
Abstract: Education is no longer safe from attacks during times of armed conflict. In many regions of the world, armed groups intentionally target schools, teachers and students and violate the right of children to get an education. Such is the case in Pakistan, where militant violence and continued armed conflict has disrupted the education of hundreds of thousands of children, particularly girls. The present study addresses a call for a better understanding of how non-governmental organisations (NGOs) function and contribute to peace-building and development through the provision of educational services in conflict zones. Based on field research, the study finds that in spite of challenges, NGOs have been playing a vital role in providing educational services to the conflict-affected communities. Disseminating information, solutions for resuming education, improving school enrolment, psychosocial support and promoting quality education lies at the forefront of NGOs' battle in the tribal areas of Pakistan. However, the state needs a comprehensive policy to protect education from violent attacks.